DAYA TARIK PASAR MODAL ISLAMI: STUDI DI BURSA EFEK INDONESIA - Zaenal Arifin (University of Merdeka Malang, 2014)
Islamic capital market was a capital market in which the stock issuers business and the trading mechanismwere both Islamic. Islamic corporate issuers were already selected in Islamic stock index while Islamic trademechanism had to meet the requirements to avoid speculation (gharar). Some experts had proposed a model ofan Islamic stock trading such as Metwally (1992) and Chapra (1992). The question was if the islamic modelwas applied, was the stock market still interesting? This study wanted to answer that question. By using asample of companies in Jakarta Islamic Index (JII) from 2007 to 2013 this study showed the following results.Metwally model proved to be very attractive because it generated a return (capital gain) at least equal to realcapital markets and the risk of capital loss was smaller. But investors should be careful because the standarddeviation of return among stock in this stock market model was relatively high. Meanwhile, the Chapra modelgave investors not only a lower risk but also lower returns. The performance of Chapra Islamic capital marketmodel had not been conclusive because when using Sharpe index and Jensen index, the performance indexdecreased but when using the Treynor index, the performance did not decrease.